Understanding Gold Toxicity in Aerobically-Grown Escherichia Coli - Vasquez-Guzman, C; Arenas-Salinas, F; Muñoz-Villagran, C; Luraschi-Vargas, R; Cornejo-Leiva, F; Contreras-Tobar, F; Figueroa, M (BioMed Central Ltd., 2020)
Background: There is an emerging field to put into practice new strategies for developing molecules with antimicrobial properties. In this line, several metals and metalloids are currently being used for these purposes, although their cellular effect(s) or target(s) in a particular organism are still unknown. Here we aimed to investigate and analyze Au3+ toxicity through a combination of biochemical and molecular approaches. Results: We found that Au3+ triggers a major oxidative unbalance in Escherichia coli, characterized by decreased intracellular thiol levels, increased superoxide concentration, as well as by an augmented production of the antioxidant enzymes superoxide dismutase and catalase. Because ROS production is, in some cases, associated with metal reduction and the concomitant generation of gold-containing nanostructures (AuNS), this possibility was evaluated in vivo and in vitro. Conclusions: Au3+ is toxic for E. coli because it triggers an unbalance of the bacterium s oxidative status. This was demonstrated by using oxidative stress dyes and antioxidant chemicals as well as gene reporters, RSH concentrations and AuNS generation. © 2020 The Author(s).